An examination of factors affecting the participation of women in macro governance: the case of women’s coalition of Zimbabwe (WCOZ 2000- 2014) - Mhuka, Tapiwa M. (Midlands State University, 2015)
Gender inequalities still characterise the leadership of Zimbabwe ,although a newly enacted constitution, Amendment number 20 and a number of international conventions ,protocols and declarations that affirm the achievement of gender equality have been signed and ratified. Literature is awash with traditional factors ( cultural, religious economic and socio political) that hinder the advancement of women in governance and leaves gaps in the context of modern factors, particularly those factors that affect African states when it comes to achieving 50/50 representation at macro level. It is from that background that the main purpose of the research sought to examine modern day factors that disturb or hinder the participation and involvement of women in macro governance that is the highest form of decision making in the private and public sector. The research focused on the experiences of the Women’s Coalition of Zimbabwe during the election period between 2000 and 2014 and incorporated political parties that is ZANU PF and the MDC T to solicit political party information. In addition three government ministries were included to gather and represent public sector information in relation to women and macro governance . Likewise NANGO ,WCoZ and the two political parties represented the private sector. In the form of a survey the research purposively identified the organisations that participated and by random sampling distributed questionnaires to respondents from the organisations under study. Premised on the Liberal Feminist theory and McFadden’s contribution to the 21stCentury ,the research’ primary data identified the differences and similarities in the status of women in public and private sector groups as well as the factors affecting the position of women. The research’ secondary data presented facts that confirmed the barriers to women’s participation in macro governance particularly during election phases. Local print media was also incorporated in the analysis of secondary data as it presented current facts in the case of the ousted Vice president, Dr J. Mujuru and its impact to the Women’s Agenda in governance issues. In light of the findings the research recommends strategies that the Civil Society in partnership with the Government of Zimbabwe need to adopt to improve the status of women in governance and advance the participation of both ordinary and influential women in Zimbabwe’s macro governance.